Pengaruh Pemberian Jenis Mulsa dan Pupuk NPK Terhadap Pertumbuhan Dan Produksi Tanaman Kacang Komak (Lablap purpureus L. sweet) - Ni Wayan Ambariani; Ni Putu Anom Sulistiawati; I Ketut Agung Sudewa (Fakultas Pertanian, Universitas Warmadewa, 2024)
This research aims to analyze the effect of providing types of mulch and NPK fertilizer on the growth and production of Komak Bean Plants (Lablap purpureus L. sweet). As well as to determine the interaction of providing types of mulch and NPK fertilizer on the growth and production of komak bean plants. This research was carried out at Br. Nyuh, Ped village, Nusa Penida District, Klungkung Regency, Bali. From May to July 2023. The research method used was a Randomized Block Design (RAK) with 2 factors arranged factorially. The first factor tested was the type of mulch (M) which consisted of 3 levels, namely: M0 as control (no mulch), M1 (silver black plastic mulch), M2 (alang alang straw mulch). The second factor tested was the use of NPK (P) fertilizer which consists of 4 levels, namely: P0 (0 kg.ha-1), P1(100 kg.ha-1), P2 (200 kg.ha-1) and P3( 300 kg.ha-1). In this way, 12 combination treatments were obtained, each repeated 3 times so that 36 plant plots were treated. The results showed that the interaction between the type of mulch and NPK fertilizer (MxP) had a very significant effect on the number of pods per plant and the length of the pods per plant. The highest pod weight per plant was obtained in the black silver plastic mulch (M1) treatment, namely 177.75 grams, an increase of 42.83% when compared to alang alang straw mulch (M2), which was only 134.92 grams. Meanwhile, the highest number of pods per plant was obtained in the black silver plastic (M2) mulch type treatment, namely 6.67 pods, an increase of 1.67% when compared to the treatment with a dose of 200 kg.ha-1(P2) NPK fertilizer, namely only 5.00 pods.